2016
DOI: 10.3329/bjms.v15i1.27149
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic syndrome in normal weight Malay subjects

Abstract: Information regarding the prevalence of features of Metabolic Syndrome (MS) in Malaysia has not been previously reported. There are also difficulties in using Western cut-off criteria to define MS in this Asian population. The aim of this study was to determine the prevalence of features of MS in normal body weight normoglycemic Malay subjects. An additional aim was to determine the optimal waist circumference cut-off which best identified MS in this population. We used data from a cross-sectional study carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Relations between different lipid parameters and insulin resistance have been studied in the past [39][40][41], and it is quite clear that there is an association between dyslipidaemia and insulin resistance. The levels of total cholesterol (TC), LDL cholesterol, and total cholesterol to HDL cholesterol ratio (TC/HDL) were significantly higher in the insulin-resistant group.…”
Section: Discussionmentioning
confidence: 99%
“…Relations between different lipid parameters and insulin resistance have been studied in the past [39][40][41], and it is quite clear that there is an association between dyslipidaemia and insulin resistance. The levels of total cholesterol (TC), LDL cholesterol, and total cholesterol to HDL cholesterol ratio (TC/HDL) were significantly higher in the insulin-resistant group.…”
Section: Discussionmentioning
confidence: 99%
“…Postmenopausal estrogen's effects on heart disease, cancer, and osteoporosis are still being discussed 12,13 . In middle-aged women Total cholesterol and low-density lipoprotein cholesterol (LDL-C) concentrations are associated with cardiovascular events and total mortality in middle-aged women and men 4,14,15 . As per the statement, the percentage of Canadians who had unhealthy levels of LDL (bad) cholesterol showed a considerable rise with increasing age.…”
Section: Methodsmentioning
confidence: 99%
“…Won et al found that a decrease in adiponectin levels correlates with an increased level of CRP and is associated with a decrease in the anti-inflammatory effect of protective adipokine. 20 Obviously, with a combination of MS and CHF, these changes can contribute to the progressive remodeling of the myocardium. In obesity, especially in its abdominal form, the hormones of adipose tissue -adipokines -act as important regulators of energy metabolism and, in particular, energy substrates in heart cells.…”
Section: Ethical Clearancementioning
confidence: 99%